Effects of an E-Learning Education Program on Knowledge and Practices of Elective Cardiac Surgery Patients - Mansin, Anutsara; Nukulkij, Pailin; Saard, Sopapan (Thai Red Cross Nursing Journal, 2023)
The purposes of this quasi-experimental research were to study the effects of an e-learning education program on the knowledge and practices of patients awaiting cardiac surgery at a tertiary hospital. The sample was composed of 99 patients; the control group consisted of 49 patients and the experimental group of 50 patients. The control group received conventional care, while the experimental group received self-directed e-learning educational program videos with comprehensive pre- and post-operative practical information for improving recovery during hospitalization. Data were collected using pre- and post-program questionnaires, as well as a post-operative practice questionnaire administered after 5 days. All research instruments in this study were validated for content by three experts. Data were analyzed by using mean, standard deviation, and independent t-test to test the difference between groups. This study revealed that the mean scores for knowledge and for post-operative practices after 5 days for the experimental group were significantly higher than those of the control group (p < .001). The results recommended that a comprehensive self-directed e-learning education program be delivered using video to successfully enhance knowledge and practices.